Large‐scale characterization study of patients with antimitochondrial antibodies but nonestablished primary biliary cholangitis. Issue 1 (10th November 2016) - Dahlqvist, Géraldine; Gaouar, Farid; Carrat, Fabrice; Meurisse, Sofia; Chazouillères, Olivier; Poupon, Raoul; Johanet, Catherine; Corpechot, Christophe; ,
Abstract : The prevalence, clinical characteristics, and outcomes of patients with antimitochondrial antibodies (AMAs), but no clinical evidence of primary biliary cholangitis (PBC), are largely unknown. A prospective study of AMA incidence was conducted through a nation‐wide network of 63 French immunology laboratories. Clinical data from 720 of 1, 318 AMA‐positive patients identified in 1 year were collected. Patients were categorized as either newly diagnosed with PBC (n = 275), previously diagnosed with PBC (n = 216), or with nonestablished diagnosis of PBC (n = 229). The latter group was specifically evaluated. Follow‐up data were collected for up to 7 years after detection of AMAs. Prevalence of AMA‐positive patients without evidence of PBC was 16.1 per 100, 000. These patients had the following characteristics: 78% female; median age 58 years; median AMA titer 1:160; extrahepatic autoimmune disorders 46%; normal serum alkaline phosphatases (ALP) 74%; ALP above 1.5 times the upper limit of normal 13%; and cirrhosis 6%. Compared to those newly diagnosed with PBC, the patients were slightly younger, had lower AMA titers, and lower sex‐ratio imbalance. Among the patients with normal ALP and no evidence of cirrhosis, the 5‐year incidence rate of PBC was 16%. Whereas no patients died from PBC, the 5‐year survival rate was 75%, as compared to 90% in a control, standardized population matched for age and sex ( P < 0.05). Conclusion : Nearly half of the newly detected AMAs in clinical practice does not lead to a diagnosis of PBC. PBC is unrecognized in 13% of those cases. Only 1 in 6 patients with AMAs and normal ALP will develop PBC after 5 years. The mortality of AMA‐positive patients without PBC is increased irrespective of the risk of PBC development. (Hepatology 2017;65:152‐163).